Measuring Health Services Utilization in Ethnic Populations: Ethnicity and Choice of Frameworks - Emmanuel Ngwakongnwi (Public Health, 2017)
Background: Health services utilization (HSU) is an important health outcome indicator, a surrogate measure of access to healthcare, that influences the outcomes of health status and consumer satisfaction, is a surrogate measure of access to healthcare. To most healthcare providers, understanding patterns of HSU is important for health system resource planning and allocation. In studies of HSU, the ethnicity variable is key especially in multicultural societies such as Canada where a significant proportion of the population consists of visible minorities, who, often are referred to in research studies as ‘underserved’ or as ‘hard-to-reach’ in the sampling context.Approach: This article discusses the relevance and utility of some frameworks for studying access to healthcare. It is intended to set the stage for a future study comprehensive systematic literature review of models of access to care and models of health system performance that address access as a criterion. To achieve this, I present selected published research on frameworks for access to medical care and HSU, including their characteristics and appropriateness for health services research. Subsequently, I briefly examine two studies that explore HSU, in Canada and the United States to determine the extent to which the selected framework or its components were employed. Finally, I describe ethnicity as a variable in the framework for HSU and conclude with limitations of this review. Conclusions: This paper has highlighted the approaches to health services utilization and the application of the Aday-Andersen framework for studies on access to care. Although this paper draws on relevant and some important contributions in the field, the assessment presented here is not exhaustive and warrants a more comprehensive review that includes recent literature on the subject.